THE INFLUENCE OF INTELLECTUAL CAPITAL AND CAPITAL STRUCTURE ON COMPANY VALUE WITH PROFITABILITY AS A MODERATION VARIABLE - Yulia Sukma Asih; Ira Hapsari; Hadi Pramono; Edi Joko Setyadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of intellectual capital and capital structure on the value of the company with profitability as a moderation variable. The study uses a quantitative approach with secondary data obtained from the financial statements of companies in the conventional banking sector listed on the Indonesia Stock Exchange for the period 2020–2024. The research sample was selected using the purposive sampling method and analyzed using panel data regression and Moderated Regression Analysis (MRA). The results of the study show that intellectual capital does not affect the value of the company but the capital structure has a positive effect on the value of the company. Profitability has been shown to strengthen the influence of intellectual capital on company value, but it is unable to moderate the influence of capital structure on company value. These findings indicate that effective management of intellectual resources and proper capital structure policies can increase the value of a company. The results of the research are expected to be a reference for company management and investors in making decisions related to increasing the company's value.